Application of game theory in inventory management - Tranamil-Vidal, Rodrigo (2014)
Game theory has been successfully applied in supply chain management problems due to its capacity of modeling situations where companies have to make strategic decisions about their production planning, inventory control and distribution systems. In particular, this article presents the application of game theory in inventory management. First, we presente the basics concepts of non-cooperative and cooperative game theory. Then, we present inventory models by means of game theory. For each model, we provide its configuration, the solution concept implemented, and the existence and uniqueness of the equilibrium used.